Pentoxifylline besides naltrexone recovers morphine‐induced inflammation in male reproductive system of rats by regulating Toll‐like receptor pathway. (7th December 2016) - Chehrei, S.; Moradi, M.; Ghiabi, H. R.; Falahi, M.; Kaviani, S.; Ghanbari, A.
Summary: This study aimed to investigate the effect of pentoxifylline on complications of prolonged usage of morphine upon the testis and sperm parameters of rats. In this study, forty male Wistar rats were divided into five groups ( n  = 8) and treated for 56 days to only saline, only morphine, only pentoxifylline, pentoxifylline + morphine and naltrexone + morphine. The diameters of seminiferous tubules, the maturity of germ line epithelium and sperm parameters were evaluated. The expression of inflammatory‐related factors in testis tissues were also investigated at gene and protein levels. The data were calculated by one‐way ANOVA test followed by Tukey's post hoc test using SPSS software for windows (version 20). Seminiferous tubule diameter, the maturity of spermatogonia and sperm parameters were significantly decreased in morphine group in comparison with control, pentoxifylline and pentoxifylline + morphine groups ( p  < .001). The expression of anti‐inflammatory markers, at both gene and protein levels, was significantly increased in testis of morphine‐treated rats in comparison with other groups ( p  < .001). Chronic morphine administration induces destructive effects on male reproductive system by regulating inflammatory responses. Pentoxifylline recovers the destructive effects of morphine on male reproductive system by inhibiting TLR (Toll‐like receptor) activity, as an anti‐inflammatory response.